Pengaruh Lama Penyimpanan Silase Daun Kelapa Sawit Terhadap Kadar Protein dan Serat Kasar - Achmad Jaelani; Aam Gunawan; Indra Asriani (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2014)
This study is aimed to acknowledge the study of the effect  of storage lenght  of palm leaf silage to Crude Protein and Crude Fiber was conducted at Pleihari, Tanah Laut District and Agriculture Laboratory of Agriculture Faculty of Lambung Mangkurat University. This Research showed that storage lenght of palm leaf silage could be affect significantly to crude fiber, but not significantly to crude protein. The storage lenght of palm leaf silage after 35 days could be   decreased   crude fiber content.